Interleaved Flyback Converter with Embedded Grid Interacting PV Cascaded MLI - Jaikrishna V; Subhranhsu Sekhar Dash; Linss T Alex; R. Sridhar (Institute of Advanced Engineering and Science, 2018)
The importance of extracting power from renewable energy sources are increasing in the modern world as the power demand is increasing day by day and the non renewable energy sources are getting dried up. Solar power is a domestic source of energy and its availability throughout the year makes it a primary target to solve this crisis. It will never produce any hazardous waste or pollution. But various issues like Power quality problems and Harmonic distortion seep in due to the intermittent nature of PV system. This paper proposes a cascaded H–bridge multilevel inverter for grid connected PV system with a flyback converter. This helps to achieve maximum power point tracking and also provides isolation which will further help to increase system efficiency. The DC–DC flyback converters are cascaded to generate multilevel output voltage. Then this multilevel dc output is given to H bridge inverter to generate multilevel output. A new control algorithm is used in this paper which combines voltage–hold Perturb and observe method and modified PWM algorithm which helps to achieve the best MPPT. The proposed topology is implemented in PSIM. The Simulation and Hardware results reveal that the suggested technique is highly.